Penggunaan Media Sosial Instagram sebagai Eksistensi Diri Bagi Generasi Z di DKI Jakarta - Novianti Tanjaya; Agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Era of globalization continues to grow. Along with the rapid development of the era, the use of the internet is more towards social networks which are now called social media. Social Media is an application that allows users to create and connect in social networks. Social media can make it easier for anyone to publish activities on social media. Instagram the most popular social media. Social media is used to fulfill self-needs and seek a self-existence for generation Z. Generation Z cannot be separated from the development of internet technology. The purpose of this study is to find out how to use Instagram as a means of self-existence for Generation Z. The research method used is a qualitative research method and uses the constructivism paradigm. Collecting data using the interview method. The results of the research are that Generation Z uses Instagram to exist, entertainment, business opportunities, forming self-image, fulfilling personal needs and spiritual needs for themselves.